Walking point : American narratives of Vietnam - Myers, Thomas (Oxford University Press, 1988)
An assessment of the most important novels and memoirs written by Americans about Vietnam, considered under the headings of realism, the classical memoir, black humour, revised romanticism. and mnemonic narrative.